Anion recognition in water by charge-neutral halogen and chalcogen bonding foldamer receptors - Borissov, A; Marques, I; Lim, JYC; Félix, V; Smith, MD; Beer, PD (American Chemical Society, 2019)
A novel strategy for the recognition of anions in water using charge-neutral σ-hole halogen and chalcogen bonding acyclic hosts is demonstrated for the first time. Exploiting the intrinsic hydrophobicity of halogen and chalcogen bond donor atoms integrated into a foldamer structural molecular framework containing hydrophilic functionalities, a series of water-soluble receptors was constructed for an anion recognition investigation. Isothermal titration calorimetry (ITC) binding studies with a range of anions revealed the receptors to display very strong and selective binding of large, weakly hydrated anions such as I- and ReO4-. This is achieved through the formation of 2:1 host-guest stoichiometric complex assemblies, resulting in an encapsulated anion stabilized by cooperative, multidentate, convergent σ-hole donors, as shown by molecular dynamics simulations carried out in water. Importantly, the combination of multiple σ-hole-anion interactions and hydrophobic collapse results in I- affinities in water that exceed all known σ-hole receptors, including cationic systems (β2 up to 1.68 × 1011 M-2). Furthermore, the anion binding affinities and selectivity trends of the first example of an all-chalcogen bonding anion receptor in pure water are compared with halogen bonding and hydrogen bonding receptor analogues. These results further advance and establish halogen and chalcogen bond donor functions as new tools for overcoming the challenging goal of anion recognition in pure water.